Optimization of Biohydrogen Production from Palm Oil Mill Effluent by Natural Microflora - Rasdi, Zatilfarihiah (2009)
Biohydrogen is a promising clean fuel as it is ultimately derived from renewable energy sources. It is environmental friendly since it burns to water, gives high energy yield, and can be produced by less energy-intensive processes. Anaerobic treatment of palm oil mill effluent (POME) was chosen to produce biohydrogen as POME is a commercially known waste that is such a burden to the industry and the environment. In this study, POME sludge was used as an inoculum to produce biohydrogen from POME. Heat-treated POME sludge acclimatised with POME incubated at 37°C for 24 h was used as a seed culture. Preliminary screening on the effects of inocula size, heat treatment, substrate concentration and pH of incubation by using a factorial design (FD) were conducted under mesophilic condition (37°C) using a serum vial (160 mL). The experimental results from two-level FD showed that pH and chemical oxygen demand (COD) of POME as substrate concentration significantly affected biohydrogen production. Optimizations of the specific hydrogen production (Ps) and the hydrogen production rate (Rm) were carried out by using a central composite design (CCD). The maximum Ps of 270 mL H2/g carbohydrate and Rm of 98 mL H2/h were obtained under optimum conditions of pH 5.86 and substrate concentration of 80 g/L. The optimized conditions obtained were subjected to a confirmation run and it showed a reproducible data with Ps of 282 mL H2/g carbohydrate and Rm of 137 mL H2/h. For the second part of experiment, 2-L of bioreactor was employed for the production of biohydrogen with and without pH control. The optimum conditions obtained in the serum vial were applied in the bioreactor. The results obtained for uncontrolled pH experiment generated 1.3 L biogas/L medium. Throughout the fermentation, no methane-gas was detected. The biohydrogen yield (Ps) was approximately 1 L H2/L medium, with hydrogen production rate (Rm) at 112 mL H2/h. For the controlled pH experiment, pH was controlled manually every 3 h at 5.86. The biogas generated from the fermentation was 2.5 L/L medium, which is almost 2-fold of biogas production from uncontrolled pH experiment. The Ps and Rm generated were 1.3 L H2/L medium and 144 mL H2/h, respectively.